“O futuro presente”: influência da inteligência artificial na qualidade de vida do consumidor - Oliveira, Dayane Renaly Lopes de (2021)
Artificial Intelligence, which is increasingly present today, has been widely used in several areas and segments, and can help society and organizations in numerous aspects. Marketers have used AI as a way to apply strategies and improve contact with consumers, mainly through mobile devices. However, it is important to understand whether these strategies are in fact effective and to what extent they can influence positively or negatively on the quality of life of the same. From this perspective, the present work brings as a general question: "What is the influence of Artificial Intelligence on the quality of life of consumers arising from consumption via mobile?" To answer the proposed question, the study is classified as qualitative and the data collection technique will be through interviews. For the description of the data, content analysis was chosen. From the results achieved, it was possible to identify that there is still a large portion of individuals who do not have knowledge about AI techniques and that marketing strategies from that use, via mobile devices, have shown feelings of discomfort, invasion, bombing in the face of consumers. With that, it is concluded that AI strategies via mobile devices have brought more negative than positive consequences on the consumer's well-being and that a more comprehensive view is needed by organizations in order to understand the individual's perception about these strategies, as well as seeking to develop more effective practices that take ethics and social responsibility into account in their marketing strategies. Thus, the study presents relevant contributions to society and organizations, in view of the knowledge awakened in society about AI and the results that serve as a basis for companies to develop better and more efficient strategies.